(3eHGOF GdGbJUGO GdgfOSj (B/s - (3GdEOQjSj, eUWai eMeO GdMSfs; (3GdLaQj, eMeO GdUGOb YHO Gddg s ((3LOI(B: s (3eQcR GdfTQ GdYdej(B, s, 2000)
(3GdebjGS GdeGdj,GdebGjjS ZjQ GdeGdjI,CgejI GdGbJUGO GdgfOSj aj GdOhd GdfGejI,eaGgje GdJcdaI,GdbjeI GdRefjI ddfbhO,bjGS bjeI GdGSJKeGQ,ebGQfI GdHOGFd hSjGSGJ GdEMdGd,GdGSJgdGc,GdJMdjd GdGbJUGOj deTGQjY GdbWGY GdYGe,JMdjd GdJYGOd,JMdjd GdeNGWQI hYOe GdJCcOs
(3GdedGMb(B:(3U(B.217-221(3;GHHdjhZQGajG(B:(3U(B.223-226 (3GdLOGhd(B:(3U(B.227-253(3;cTGa GdeUWdMGJ(B:(3U(B.255-2269s
Keywords: (3GdGbJUGO GdgfOSjs